Effect of Cromakalim Prodrug 1 (CKLP1) on Aqueous Humor Dynamics and Feasibility of Combination Therapy With Existing Ocular Hypotensive Agents - Roy Chowdhury, Uttio (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: Cromakalim prodrug 1 (CKLP1) is a water-soluble ATP-sensitive potassium channel opener that has shown ocular hypotensive properties in ex vivo and in vivo experimental models. To determine its mechanism of action, we assessed the effect of CKLP1 on aqueous humor dynamics and in combination therapy with existing ocular hypotensive agents. METHODS: Outflow facility was assessed in C57BL/6 mice by ex vivo eye perfusions and by in vivo constant flow infusion following CKLP1 treatment. Human anterior segments with no trabecular meshwork were evaluated for effect on pressure following CKLP1 treatment. CKLP1 alone and in combination with latanoprost, timolol, and Rho kinase inhibitor Y27632 were evaluated for effect on intraocular pressure in C57BL/6 mice and Dutch-belted pigmented rabbits. RESULTS: CKLP1 lowered episcleral venous pressure (control: 8.9 ± 0.1 mm Hg versus treated: 6.2 ± 0.1 mm Hg, P < 0.0001) but had no detectable effect on outflow facility, aqueous humor flow rate, or uveoscleral outflow. Treatment with CKLP1 in human anterior segments without the trabecular meshwork resulted in a 50% ± 9% decrease in pressure, suggesting an effect on the distal portion of the conventional outflow pathway. CKLP1 worked additively with latanoprost, timolol, and Y27632 to lower IOP, presumably owing to combined effects on different aspects of aqueous humor dynamics. CONCLUSIONS: CKLP1 lowered intraocular pressure by reducing episcleral venous pressure and lowering distal outflow resistance in the conventional outflow pathway. Owing to this unique mechanism of action, CKLP1 works in an additive manner to lower intraocular pressure with latanoprost, timolol, and Rho kinase inhibitor Y27632.